Google-haut Suomen asuntojen hintojen ennustajana; Predicting Housing Prices with Google Searches in Finland - Joona Widgrén (The Research Institute of the Finnish Economy (ETLA), 2016)
– This report examines whether Google search queries can be used to predict the present and the near future house prices in Finland. Compared to a simple benchmark model, Google searches improve the prediction of the present house price index by 7.5 % measured by mean absolute error. In addition, search queries improve the forecast of near future house prices. Predicting the present and near future house prices is relevant information to many agents, such as realtors and political decision makers.
Keywords: C1; C22; C43; C53; C82; E27; 330; Google Trends; Internet; Nowcasting; Forecasting; Housing market; Time series; Prognoseverfahren; Online-Recherche; Immobilienpreis; Zeitreihenanalyse; Finnland